Padre Ignacio; Or, The Song of Temptation - Wister, Owen, 1860-1938 (Salt Lake City, UT : Project Gutenberg, 1998)
"Padre Ignacio; Or, The Song of Temptation" by Owen Wister is a novel written in the late 19th century, specifically during a time when Western America was still being vividly captured in literature. The book grapples with themes of temptation, sacrifice, and the internal conflict between worldly desires and spiritual commitments. It follows the life of Padre Ignacio, a priest stationed at a California mission, who faces the lure of his past life when a young, charming musician named Gaston Villere visits the mission. The narrative revolves around Padre Ignacio's reflections on his life, his yearning for the cultural richness of his youth in Europe, and his duties to his parishioners. The arrival of Gaston stirs deep emotions within Ignacio, awakening his longing for the world he left behind. Their conversations touch on music, art, and the notion of contentment with simple living contrasted against the vibrant lure of worldly pleasures. Ultimately, the novel delves into themes of renunciation, as Ignacio grapples with the realization that pursuing fleeting joys can lead to spiritual turmoil. As tragedy strikes with Gaston's untimely death, Ignacio finds resolution through his connection to his teaching and the community he cherishes, illustrating the profound impact of personal sacrifice and the enduring search for peace. (This is an automatically generated summary.)
Release date is 1998-07-01
Produced by Bill Brewer, and David Widger
Keywords: Priests -- Fiction; Missions -- California -- Fiction